Interleukin 12 as an Adjuvant to WI-1 Adhesin Immunization Augments Delayed-Type Hypersensitivity, Shifts the Subclass Distribution of Immunoglobulin G Antibodies, and Enhances Protective Immunity to Blastomyces dermatitidis Infection - Wüthrich, Marcel (American Society for Microbiology, 2000)
Cell-mediated immunity is pivotal in host resistance to Blastomyces dermatitidis infection. Immunization of mice with the WI-1 adhesin enhances resistance against experimental pulmonary infection but elicits features of a mixed T-helper-cell immune response. Immune mice acquire delayed-type hypersensitivity (DTH) but also high titers of WI-1-specific immunoglobulin G1 (IgG1) and IgG2b, a result indicative of T-helper-2 cellular immunity. We report that interleukin-12, used as an adjuvant for WI-1 immunization, augments DTH, shifts the balance of the T-helper phenotype toward Th1, and enhances resistance to B. dermatitidis infection.